Detection of Virtually All Mutations-SSCP (DOVAM-S): A Rapid Method for Mutation Scanning with Virtually 100% Sensitivity. (May 1999) - Liu, Q.; Feng, J.; Buzin, C.; Wen, C.; Nozari, G.; Mengos, A.; Nguyen, V.; Liu, J.; Crawford, L.; Fujimura, F.K.; Sommer, S.S.
Dideoxy fingerprinting (ddF) was used as a tool to search for a generic set of conditions with sufficient power to detect virtually all mutations. For each condition tested, a very large sample of mutation-containing, single-stranded segments (about 1500) were analyzed with ddF. Correlation coefficients identified pairs of conditions in which single-strand conformation polymorphism (SSCP) mobilities were poorly correlated. The data strongly suggest that tertiary structure (e.g., base-sugar and sugar-sugar interactions) rather than secondary structure is the predominant determinant of mobility shifts by SSCP. Five conditions were selected with sufficient redundancy to detect all the mutations. The sensitivity of detection of virtually all mutations-SSCP (DOVAM-S) was determined by blinded analyses on samples containing additional mutations scattered throughout the eight exons and splice junctions in the factor IX gene. The factor IX gene sequence (2.5 kb) was scanned in one lane by 15 PCR-amplified segments (125 kb of sequence scanned per gel). All of the 84 single-base substitutions were detected in the blinded analyses, the first consisting of 50 hemizygous mutant and wild-type (WT) samples and the second consisting of 50 heterozygous mutant and WT samples. DOVAM-S is estimated to be five times faster than fluorescent DNA sequencing for the detection of virtually all mutations when the five conditions are applied.